Complicated Grief, Depression and Post-Traumatic Stress Symptoms Among Bereaved Parents following their Child's Death in the Pediatric Intensive Care Unit: A Follow-Up Study. (February 2022) - Suttle, Markita; Hall, Mark W.; Pollack, Murray M.; Berg, Robert A.; McQuillen, Patrick S.; Mourani, Peter M.; Sapru, Anil; Carcillo, Joseph A.; Startup, Emily; Holubkov, Richard; Dean, J. Michael; Notterman, Daniel A.; et al.
Background: Parents often suffer reduced mental health after their child's death; however, the trajectory and risk factors are not well described. Objective: Describe the change in complicated grief, depression, and post-traumatic stress symptoms among parents between 6 and 13 months after their child's death in a pediatric intensive care unit (PICU), and factors associated with 13-month symptoms. Methods: Parents whose children died in 1 of 8 PICUs affiliated with the Collaborative Pediatric Critical Care Research Network completed surveys 6 and 13 months after their child's death. Surveys included the Inventory of Complicated Grief (ICG), the Patient Health Questionnaire-8 (PHQ-8) for depression, and the Short Post-Traumatic Stress Disorder Rating Interview (SPRINT). Parents provided sociodemographics. Charts were reviewed for child characteristics. Results: One-hundred and fifty seven parents of 104 deceased children completed surveys at both time points. Mental health symptoms declined over time (mean (SD)): ICG (33.8 (15.4) vs. 30.5 (15.2), p < 0.001), PHQ-8 (9.0 (6.4) vs. 7.3 (5.8), p < 0.001), and SPRINT (14.1 (8.3) vs. 12.0 (8.2), p < 0.001). After controlling for 6-month scores, higher 13-month ICG was independently associated with sudden unexpected death; higher PHQ-8 with Black race, insecure attachment style, and sudden unexpected death; and higher SPRINT with having a high school level of education (compared to college degree or higher). Conclusion: Mental health symptoms improve among parents during the first 13 months after their child's death; however, symptoms persist for many. Black parents and those whose children die suddenly may be high risk for poor adjustment during bereavement.